Medial Portal Placement for ACL Femoral Tunnel Drilling With an Over-the-Top Guide: Concepts and Technique - Travis Baes MD; Michael Gaudiani MD; Vasilios Moutzouros MD (Video Journal of Sports Medicine)
Background: The rate of graft failure after anterior cruciate ligament (ACL) reconstruction ranges from 3% to 22%. Surgeons must mitigate risks of failure by limiting technical errors. Femoral tunnel malposition has been cited as the most common technical error associated with ACL reconstruction. As such, techniques for femoral tunnel drilling have evolved to ensure placement of the tunnel within the anatomic footprint of the native ACL. If using an over-the-top guide, the placement of the medial portal becomes critical to ensure safe and accurate drilling. Indications: The purpose of this video is to highlight key concepts related to the proper placement of the medial portal during ACL reconstruction when using an over-the-top guide and low-profile reamer. Technique Description: A skin marking for the planned medial portal is made approximately 1.5 to 2 cm medial to the patellar tendon while palpating the joint line. After standard bone–patella tendon–bone (BTB) autograft harvest and anterolateral portal establishment, the medial portal is created under direct visualization, utilizing an 18-gauge spinal needle to ensure proper trajectory for over-the-top femoral tunnel drilling. After the tibial tunnel is prepared, the over-the-top guide is inserted via the medial portal and hooked onto the back wall. The knee is then hyperflexed and the beath pin is advanced out the lateral thigh. The low-profile reamer is advanced over the wire and reamed to the desired tunnel depth. The back wall integrity is confirmed and the prepared autograft is then passed and secured via interference screw fixation. Results: This technique provides a consistent and reproducible method of femoral tunnel placement in the anatomic footprint of the ACL without damaging the medial femoral condyle. We can also instrument through the same portal to treat meniscal pathology without necessitating an accessory medial portal. Discussion/Conclusion: Appropriate medial portal placement for femoral tunnel drilling with an over-the-top guide is critical for safe, reproducible, and consistent tunnel location. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.